MACROZOOBENTHOS COMMUNITY AS BIOINDICATOR OF WATER QUALITY FOR FISH CULTIVATION IN THE AIR DUREN RIVER, BANGKA REGENCY - Putri, Yussa; Kurniawan, Ardiansyah; Kurniawan, Andri (Journal of Aquatropica Asia, 2023)
Rivers are one source of water that is often used by humans for their life activities and the habitat for organisms that live in these waters. The quality decreases due to pollutants originating from domestic waste, both liquid waste and solid waste, and is also polluted by difficult organic compounds/chemicals. degraded such as detergents, phosphates or other compounds. One type of aquatic organism that is influenced by changes in the environment and water quality is macrozoobenthos, the sensitivity of macrobenthos to changes that occur in the water, making macrobenthos an indicator of the condition of a water area. This research aims to determine the diversity of macrozoobenthos as a bioindicator of water quality for fish cultivation in the Air Duren River Stream and to determine the water quality of the Air Duren River Stream for Aquaculture activities. Sampling was carried out in the Air Duren River using benthos filters. and analysis at the Aquaculture Laboratory, Faculty of Agriculture, Fisheries and Biology, Bangka Belitung University. Based on the results, it is known that the macrozoobenthos encountered were 6 species with a moderate level of diversity